Groundwater legal protection in Malaysia : lessons from UK experience / Norma Abu Hanifah - Abu Hanifah, Norma (Faculty of Administratron and Law, 2001)
In modern industrial societies, surface water quality is fast deteriorating because of pollution from urban and industrial waste, improper management of land development works and poor control of agricultural activities. In Malaysia, studies conducted by the Department of Environment in monitoring the quality of rivers for five years (1989-1993) reveal that, although the number of heavily polluted rivers remained unchanged, the number of slightly polluted rivers increased from 44 in 1991 to 56 in 1992.1 The overall water quality in 1995 had deteriorated at a rate of 0.55%.2 The increase in pollution and misuse of surface water has resulted in an urgent need for alternative sources of water supply. The development of groundwater as a supplementary source of water supply is the natural choice. However, the legislative framework for the control of groundwater in Malaysia has risen in an ad hoc fashion over the years.